Responding to Climate Change Crises: Firms' Trade‐Offs - FRITSCH, FELIX; ZHANG, QI; ZHENG, XIANG (Journal of Accounting Research, 2025)
ABSTRACT We examine firms' trade‐offs in their voluntary disclosure decisions following negative media coverage of climate change incidents. By combining a keyword discovery algorithm and a fine‐tuned BERT model, we identify “hard” and “soft” climate disclosures on Twitter. Our findings indicate that firms tend to issue climate tweets as a rapid response to negative climate incidents. Additionally, firms with a history of hard climate change disclosure, as measured by ESG reports, are more likely to issue climate‐related responses than firms without such a history. Furthermore, we show that prior hard disclosure is associated with hard responses when the incident receives moderate media attention, but with soft responses when the incident receives low media attention. Our findings provide empirical insights for dynamic disclosure theory by illustrating how prior disclosure shapes firms' response strategies to negative media coverage.